The Effect of Different Dose of Rifampicin on Induction Apoptosis in Renal Cells of Male White Rats - A. Ghazzay, Ali (International Journal of Psychosocial Rehabilitation, 2020)
The present study was aimed at detecting the effect of rifampicin on the apoptotic pathway in the rat renal cells. The experimental animals were divided randomly into four groups, each group consisting of 10 rats. Group 1 was considered the control group and was administered water for a period of days, while the rest of the groups were administered a gastric dose (50, 100, or 150 mg) for a period of 28 days. The period of rifampicin started to promote apoptosis in renal cells, which was evaluated histologically by scanning electron microscopy (S.E.M.) techniques. s Tissue of animals treated with the low dose of rifampicin showed small blebs on the surface of the outer cell with few pores in it, and the surface in general appeared smooth with the presence of red blood cells indicating bleeding, while the animals treated with the moderate dose showed the presence of more numerous blebs than the low group, and the outer surface appeared rough and perforated, while for the group of animals treated with the high dose, it showed the presence of many blebs with a clear perforation of the surface.